High‐Performance Polycrystalline Silicon Thin‐Film Transistors without Source/Drain Doping by Utilizing Anisotropic Conductivity of Bridged‐Grain Lines. (1st December 2019) - Zhang, Meng; Lin, Haotao; Deng, Sunbin; Chen, Rongsheng; Li, Guijun; Han, Su‐Ting; Zhou, Ye; Yan, Yan; Zhou, Wei; Wong, Man; Kwok, Hoi‐Sing
Abstract: By utilizing anisotropic conductivity of bridged‐grain (BG) lines, a polycrystalline silicon (poly‐Si) thin‐film transistor (TFT) without source/drain (S/D) doping is designed, simulated, and fabricated. In the new design, the current is made to flow along the BG lines in the S/D region and flow perpendicularly to the BG lines in the channel. By taking advantage of the anisotropic conductivity of the BG lines, the S/D doping process is eliminated and the fabrication process cost is reduced. Meanwhile, the advantages of adopting BG lines are maintained. The as‐fabricated TFTs without S/D doping exhibit excellent device characteristics, compared with normal TFTs. The reliability of TFTs without S/D doping is also evaluated under hot carrier stress and negative/positive bias stress. Additionally, the proposed new TFT structure allows a wider range of dopant activation conditions. Abstract : By utilizing anisotropic conductivity of bridged‐grain lines, a polycrystalline silicon thin‐film transistor (TFT) without source/drain (S/D) doping is designed, simulated, and fabricated. The as‐fabricated TFTs without S/D doping exhibit excellent device characteristics. By eliminating the S/D doping process, the fabrication cost is reduced. Additionally, the proposed TFT structure allows a wider range of dopant activation conditions compared with the normal structure.